Structural Equilibrium Configuration of Benzene and Aniline: A First-Principles Study - Rai, Krishna Bahadur; Ghimire, Rishi Ram; Dhakal, Chandra; Pudasainee, Kiran; Siwakoti, Bijay (Journal of Nepal Chemical Society, 2024)
The present work describes the equilibrium configuration of aromatic compounds like benzene and aniline molecules using the first principle (ab initio) calculation method implemented by the Gaussian 98 programs. The ground state energy for benzene and aniline molecules obtained using the DFT (B3LYP) calculation is lower than that obtained with the HF+MP2 method which, in turn, is lower than that obtained with the HF calculation. The calculated values of bond length, bond angle, and dihedral angle for these molecules with HF, HF+MP2, and DFT (B3LYP) levels of calculation agree with each other within 2%. The calculated C-C and C-H bond lengths of the benzene molecule are 1.394 Å and 1.084 Å at DFT (B3LYP) calculation and these values agree well with the experimental value of 1.395 Å and 1.084 Å for C-C and C-H bond. Also, the calculated value of bond angles and dihedral angles for benzene molecule are 120° and 180° respectively. For aniline molecule, the C-N and N-H bond lengths are found 1.378 Å and 1.003 Å respectively at DFT (B3LYP) calculation, which agrees with the experimental value of C-N and N-H bond lengths with values of 1.475 Å and 1.008 Å within 7% respectively. For the benzene molecule, there is a symmetrical charge distribution. The total dipole moment of the benzene molecule is zero, indicating that the centers of positive and negative charge coincide with each other such that the benzene molecule is non-polar whereas aniline is a polar molecule with a dipole moment of 1.9828 Debye